2006
DOI: 10.1002/bip.20644
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo confocal Raman study of human skin hydration: Assessment of a new moisturizing agent, pMPC

Abstract: The hydration capacities of a biomimetic polymer, 2-methacryloyloxethylphosphorylcholine polymer (pMPC), alone and microencapsulated, in association with another well known hydrating polymer, Hyaluronic acid, were investigated in vitro on skin models and in vivo on volunteers by using confocal Raman microspectroscopy. The hydration impact and the relative water content in the Stratum corneum were calculated from the Raman spectra using the OH (water)/CH3 (protein) ratio. Moreover, the follow-up of the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…Among Raman markers of skin hydration, the ratio of the integrated intensities I (3350–3550) /I (2910–2965) (OH stretching vibration of water (ν OH )/CH 3 stretching vibration attributed to skin protein (ν C–H of CH3 )) has been considered in several renowned publications as a reference indicator to measure water in skin and also to assess the moisturizing power of dermo‐cosmetic agents at the level of the stratum corneum and the epidermis . We tested this method to determine the water concentration in our dermal skin samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Raman markers of skin hydration, the ratio of the integrated intensities I (3350–3550) /I (2910–2965) (OH stretching vibration of water (ν OH )/CH 3 stretching vibration attributed to skin protein (ν C–H of CH3 )) has been considered in several renowned publications as a reference indicator to measure water in skin and also to assess the moisturizing power of dermo‐cosmetic agents at the level of the stratum corneum and the epidermis . We tested this method to determine the water concentration in our dermal skin samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Raman spectroscopy was proven to be a sensitive technique to probe the degradation of the stroma by matrix metalloproteinases in basal cell carcinoma . The potential of confocal Raman microspectroscopy for monitoring skin hydration has also been demonstrated . This non‐invasive technique allows in‐depth measurements of the water concentration from the surface to several tens of microns below the skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…Chrit et al have used confocal Raman spectroscopy to assess the extent of skin hydration changes after using a glycerol-based moisturizing product in vivo [ 34 ] and were able to classify different hydrating products depending on their moisturizing effect on the skin. They showed that a polyphospholipid (poly [2-methacryoyloxylphosphorylcholine or pMPC]) was able to increase water levels in the skin, both in vivo and in vitro, although it should be noted that dosing of the products was not tightly controlled, with any excess product being removed after application and before analysis [ 35 ] . Recently, Förster et al used confocal Raman microscopy to monitor the penetration of retinol into pig skin, and how formulation differences affect penetration [ 36 ] .…”
Section: Cosmetic Ingredientsmentioning
confidence: 98%
“…For example, water concentration as it varies across the SC is calculated from ratioing the water signal against the combined signal from water and protein within the skin. This method has also been used to estimate differences in SC thickness in vivo at different body sites and during aging [ 45,46 ] and to evaluate the effects of water and moisturizing ingredients on SC hydration, after both short-term treatment [ 34,47 ] and long-term treatment [ 48 ] . The majority of current research which is using Raman to look at the skin focuses on the SC and upper layers of the viable epidermis, as light becomes increasingly scattered as it penetrates more deeply, reducing signal strength and making data collection more diffi cult.…”
Section: In Vivo Confocal Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation